Collisional N-body dynamics coupled to self-gravitating magnetohydrodynamics reveals dynamical binary formation - Wall, Joshua E.; McMillan, Stephen; Klessen, Ralf S. (The astrophysical journal, 2019)
We describe a star cluster formation model that includes individual star formation from self-gravitating, magnetized gas, coupled to collisional stellar dynamics. The model uses the Astrophysical Multi-purpose Software Environment to integrate an adaptive-mesh magnetohydrodynamics code (FLASH) with a fourth order Hermite N-body code (ph4), a stellar evolution code (SeBa), and a method for resolving binary evolution (multiples). This combination yields unique star-formation simulations that allow us to study binaries formed dynamically from interactions with both other stars and dense, magnetized gas subject to stellar feedback during the birth and early evolution of stellar clusters. We find that for massive stars, our simulations are consistent with the observed dynamical binary fractions and mass ratios. However, our binary fraction drops well below observed values for lower mass stars, presumably due to unincluded binary formation during initial star formation. Further, we observe a buildup of binaries near the hard-soft boundary that may be an important mechanism driving early cluster contraction.
Gesehen am 04.02.2020